The Evaluation of Industrial Intership (Prigel) Program for UNNES Beauty Education Students Using the CIPP Model - Pritama, Delfilia Putri; Ali Achmadi, Taofan Ali Achmadi (Jurnal Profesi Keguruan, 2025)
This study aims to evaluate the implementation of the Unnes Prigel program using the CIPP evaluation model (Context, Input, Process, Product). The research method employed is descriptive quantitative with data collection techniques through questionnaires, supported by interviews. The study population includes students of the Beauty Education Study Program at UNNES who have participated in the Unnes Prigel program, the Unnes Prigel Program Coordinator in the Faculty of Engineering UNNES, and Prigel industry partners. The results show that in terms of Context, the Unnes Prigel program has goals aligned with the needs of the beauty industry and supports the MBKM policy, although some challenges remain in its implementation. Regarding Input, student preparedness, lecturer involvement, and industry support are relatively good, though issues persist in course recognition regulations and facility limitations. In the Processaspect, the program runs quite effectively, but there are still obstacles in communication and coordination between the university and industry. In the Product aspect, the program provides significant benefits in improving students' technical (hard skills) and non-technical (soft skills) abilities, although there is still feedback related to the evaluation system and the sustainability monitoring of the program. The conclusion of this research is that the Unnes Prigel program has had a positive impact on preparing students for the workforce but still requires improvement in regulation, coordination, and program evaluation aspects.